The effect of age and body composition on body mass estimation of males using the stature/bi-iliac method. Issue 115 (February 2018) - Junno, Juho-Antti; Niskanen, Markku; Maijanen, Heli; Holt, Brigitte; Sladek, Vladimir; Niinimäki, Sirpa; Berner, Margit
Abstract: The stature/bi-iliac breadth method provides reasonably precise, skeletal frame size (SFS) based body mass (BM) estimations across adults as a whole. In this study, we examine the potential effects of age changes in anthropometric dimensions on the estimation accuracy of SFS-based body mass estimation. We use anthropometric data from the literature and our own skeletal data from two osteological collections to study effects of age on stature, bi-iliac breadth, body mass, and body composition, as they are major components behind body size and body size estimations. We focus on males, as relevant longitudinal data are based on male study samples. As a general rule, lean body mass (LBM) increases through adolescence and early adulthood until people are aged in their 30s or 40s, and starts to decline in the late 40s or early 50s. Fat mass (FM) tends to increase until the mid-50s and declines thereafter, but in more mobile traditional societies it may decline throughout adult life. Because BM is the sum of LBM and FM, it exhibits a curvilinear age-related pattern in all societies. Skeletal frame size is based on stature and bi-iliac breadth, and both of those dimensions are affected by age. Skeletal frame size based body mass estimation tends to increase throughout adult life in both skeletal and anthropometric samples because an age-related increase in bi-iliac breadth more than compensates for an age-related stature decline commencing in the 30s or 40s. Combined with the above-mentioned curvilinear BM change, this results in curvilinear estimation bias. However, for simulations involving low to moderate percent body fat, the stature/bi-iliac method works well in predicting body mass in younger and middle-aged adults. Such conditions are likely to have applied to most human paleontological and archaeological samples.